Spin reflection-induced field-free magnetization switching in perpendicularly magnetized Mgo/Pt/Co heterostructures - Jin, Tianli (2022)
Field-free magnetization switching is critical towards practical, integrated spin-orbit torque (SOT)-driven magnetic random-access memory with perpendicular magnetic anisotropy. Our work proposes a technique to modulate the spin reflection and spin density of states within a heavy-metal Pt through interfacing with a dielectric MgO layer. We demonstrate tunability of the effective out-of-plane spin torque acting on the ferromagnetic Co layer, enabling current-induced SOT magnetization switching without the assistance of an external magnetic field. The influence of the MgO layer thickness on effective SOT efficiency shows saturation at 4 nm, while up to 80% of field-free magnetization switching ratio is achieved with the MgO between 5 and 8 nm. We analyze and attribute the complex interaction to spin reflection at the dielectric/heavy metal interface and spin scattering within the dielectric medium due to interfacial electric fields. Further, through substituting the dielectric with Ti or Pt, we confirm that the MgO layer is indeed responsible for the observed field-free magnetization switching mechanism.